Reduced P-glycoprotein recognition of a radioiodine-labeled phosphonium cation by stilbenylation for mitochondrial membrane potential based-imaging. (15th April 2023) - Suzuki, Chie; Sakai, Toshihiro; Magata, Yasuhiro
Graphical abstract: Abstract: The accumulation of radiolabeled phosphonium cations in cells is dependent on the mitochondrial membrane potential (MMP). However, the efflux of these cations from tumor cells via P-glycoprotein (P-gp) limits their clinical application as MMP-based imaging tracers. In the present study, we designed ( E )-diethyl-4-[ 125 I]iodobenzyl-4-stilbenylphosphonium ([ 125 I]IDESP), which contains a stilbenyl substituent, as a P-gp inhibitor to reduce P-gp recognition, and evaluated its biological properties in comparison with 4-[ 125 I]iodobenzyl dipropylphenylphosphonium ([ 125 I]IDPP). The in vitro cellular uptake ratio of [ 125 I]IDESP in P-gp expressing K562/Vin cells to the parent (P-gp negative) K562 cells was significantly higher than that of [ 125 I]IDPP. The efflux rate of [ 125 I]IDESP was not significantly different between K562 and K562/Vin, while [ 125 I]IDPP was rapidly effluxed from K562/Vin compared with K562, and the efflux of [ 125 I]IDPP from K562/Vin was inhibited by the P-gp inhibitor, cyclosporine A. The cellular uptake of [ 125 I]IDESP was well correlated with the MMP levels. These results suggested that [ 125 I]IDESP was accumulated in cells depending on the MMP levels, without being effluxed via P-gp, while [ 125 I]IDPP was rapidly effluxed from the cells via P-gp. Despite having suitable in vitro properties for MMP-based imaging, [ 125 I]IDESP showed rapid blood clearance and lower tumor accumulation than [ 125 I]IDPP. Improvement in the normal tissue distribution of [ 125 I]IDESP is required to develop an agent for use in in vivo MMP-based tumor imaging.